171k views
25 votes
HELP ME PLEASE REAL ANSWERS ONLY

HELP ME PLEASE REAL ANSWERS ONLY-example-1
User Neetu
by
4.6k points

1 Answer

9 votes

Answer: x=4, x=-5

Explanation:


(x)/(x-4)-(4)/(x+5)=(36)/(x^2+x-20)

Multiply everything by the LCM = (x-4)(x+5):


(x)/(x-4)\left(x-4\right)\left(x+5\right)-(4)/(x+5)\left(x-4\right)\left(x+5\right)=(36)/(x^2+x-20)\left(x-4\right)\left(x+5\right)


(x\left(x-4\right)\left(x+5\right))/(x-4) -(4\left(x-4\right)\left(x+5\right))/(x+5) =(36\left(x-4\right)\left(x+5\right))/(\left(x-4\right)\left(x+5\right))

Simplify by cancelling out same terms: in the numerators and denominators:


x\left(x+5\right)-4\left(x-4\right)=36


x^2+x-20=0

(x+5)(x-4) = 0

The solution to the quadratic equation is x=4, x=-5

User John Eikenberry
by
4.9k points